Formulation and evaluation of a pineapple and strawberry pasteurized pulp mix (Agroindustrial Science, 2019)
Research purpose was to formulate and evaluate a pulp from pineapple and strawberry, which were selected due to high consumption in the province of Chimborazo, since they provide pleasant organoleptic characteristics to the final consumer. Pulp properties were moisture content between 83% to 88%, moreover pH content of 4.65, Vitamin C content of 0.03 and Iron content of 33.32, we have found. In relation to the microbiological analysis we obtained absence of total coliforms, absence of fecal coliforms, Molds and yeasts 70, an antioxidant activity was determined and total polyphenols of (10-58 mg/ 100 g). Mixture Fruits were subjected to experimental design with two-factorial experiment where Treatment 3 with 60% pineapple and 30% strawberry is the one that had the best response. The product stands out for its antioxidant capacity and maintains a close relationship with the photochemical components, specifically the phenolic compounds.